Emotive politeness in face-threatening speech acts: cross-cultural perspectives - Larina, Tatiana V. (Slovo.ru : Baltiĭskiĭ akt͡s︡ent, 2025)
The discursive approach to the study of politeness has expanded its scope by incorporating the hearer, in addition to the speaker, as well as the context of interaction, which determines various aspects of communication, including the emotional/emotive dimension. This article examines politeness through the prism of the emotional component of communication. It contributes to the study of emotive politeness, which focuses on the recipient's feelings, in face-threatening acts. The purpose of this study is to identify the means of mitigating refusal through emotional support to the addressee in English and Russian academic digital communication and to trace their culture-specific variability. The material consists of authentic Russian and English emails that contain a refusal to a request to write a review of an article and a refusal to an invitation to contribute to a special issue of a journal. The study focuses on the structure of refusal, the ways it is performed, supporting moves that aim to mitigate its threat, as well as combinations of these and their conventional features. Contrastive analysis draws on the main provisions of emotive lingua-ecology, cross-cultural pragmatics, the theory of (im)politeness and communicative ethnostyles. Taking into account the fact that each e-mail may have its own features, predetermined by the author’s idiostyle and psychological characteristics, as well as the context of the exchange, we have identified some culture-specific features. The findings suggest that English emails are more focused on mitigating refusal and its negative effect on the addressee’s feelings, thereby saving face, compared with the Russian ones. This can be observed in the structure of refusal, its supporting moves and politeness strategies. The results confirm that politeness is not only a social, but also a psychological phenomenon based on empathy and tact. Emotive politeness, its manifestations and relevance may vary across cultures and are shaped by the values shared by its representatives.